Pyrene Molecular Orbital Shuffle—Controlling Excited State and Redox Properties by Changing the Nature of the Frontier Orbitals. Issue 53 (21st August 2017) - Merz, Julia; Fink, Julian; Friedrich, Alexandra; Krummenacher, Ivo; Al Mamari, Hamad H.; Lorenzen, Sabine; Haehnel, Martin; Eichhorn, Antonius; Moos, Michael; Holzapfel, Marco; Braunschweig, Holger; Lambert, Christoph; et al.
Abstract: We show that by judicious choice of substituents at the 2‐ and 7‐positions of pyrene, the frontier orbital order of pyrene can be modified, giving enhanced control over the nature and properties of the photoexcited states and the redox potentials. Specifically, we introduced a julolidine‐like moiety and Bmes2 (mes=2, 4, 6‐Me3 C6 H2 ) as very strong donor (D) and acceptor (A), respectively, giving 2, 7‐D‐π‐D‐ and unsymmetric 2, 7‐D‐π‐A‐pyrene derivatives, in which the donor destabilizes the HOMO−1 and the acceptor stabilizes the LUMO+1 of the pyrene core. Consequently, for 2, 7‐substituted pyrene derivatives, unusual properties are obtained. For example, very large bathochromic shifts were observed for all of our compounds, and unprecedented green light emission occurs for the D/D system. In addition, very high radiative rate constants in solution and in the solid state were recorded for the D‐π‐D‐ and D‐π‐A‐substituted compounds. All compounds show reversible one‐electron oxidations, and Jul2 Pyr exhibits a second oxidation, with the largest potential splitting (Δ E =440 mV) thus far reported for 2, 7‐substituted pyrenes. Spectroelectrochemical measurements confirm an unexpectedly strong coupling between the 2, 7‐substituents in our pyrene derivatives. Abstract : Doing the orbital shuffle : 2, 7‐D‐π‐D‐ and unsymmetric 2, 7‐D‐π‐A‐pyrene derivatives, based on a julolidine‐like moiety as very strong donor (D) and Bmes2 (mes=2, 4, 6‐Me3 C6 H2 ) as acceptor (A), have been prepared and show unusual photophysics, such as large bathochromic shifts and high radiative rate constants, and unprecedented green light emission for the D/D system. Spectroelectrochemical measurements indicate strong coupling between the 2‐ and 7‐substituents.